2013
DOI: 10.1111/jne.12028
|View full text |Cite
|
Sign up to set email alerts
|

Lactation Reduces Glial Activation Induced by Excitotoxicity in the Rat Hippocampus

Abstract: Motherhood induces a series of adaptations in the physiology of the female, including an increase of maternal brain plasticity and a reduction of cell damage in the hippocampus caused by kainic acid (KA) excitotoxicity. We analysed the role of lactation in glial activation in the hippocampal fields of virgin and lactating rats after i.c.v. application of 100 ng of KA. Immunohistochemical analysis for glial fibrillary acidic protein (GFAP) and ionised calcium binding adaptor molecule 1 (Iba-1), which are marker… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 59 publications
0
15
0
Order By: Relevance
“…For example, progesterone has been found to be anti-inflammatory in the face of an ischemic challenge, nerve damage, or even infection (Brotfain et al, 2016; Kipp et al, 2016; Labombarda et al, 2015; Lammerding et al, 2016; Paris et al, 2016; Perez-Alvarez and Wandosell, 2016). Additionally, during lactation, progesterone contributes to an increase in astrocytes in the rodent cingulate cortex (Salmaso et al, 2009) and the dentate gyrus of the hippocampus (Cabrera et al, 2013). Therefore it is very likely that high levels of progesterone associated with pregnancy can impact the function of glial cells, including microglia, thereby altering the expression of cytokines throughout pregnancy and the postpartum period (Posillico and Schwarz, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…For example, progesterone has been found to be anti-inflammatory in the face of an ischemic challenge, nerve damage, or even infection (Brotfain et al, 2016; Kipp et al, 2016; Labombarda et al, 2015; Lammerding et al, 2016; Paris et al, 2016; Perez-Alvarez and Wandosell, 2016). Additionally, during lactation, progesterone contributes to an increase in astrocytes in the rodent cingulate cortex (Salmaso et al, 2009) and the dentate gyrus of the hippocampus (Cabrera et al, 2013). Therefore it is very likely that high levels of progesterone associated with pregnancy can impact the function of glial cells, including microglia, thereby altering the expression of cytokines throughout pregnancy and the postpartum period (Posillico and Schwarz, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Research in our laboratory has used the postpartum period of lactation as a model of physiological hyperprolactinaemia and has shown that the rat dam is less sensitive to neurotoxic damage during lactation than virgin conspecifics. More specifically, the dam presents a significant local up‐regulation of antiapoptotic protein Bcl‐2 levels compared to dioestrus virgin rats under basal conditions, and lower cell death (FJC) and apoptosis (terminal deoxynucleotidyl transferase dUTP nick end labelling), no significant loss of neurones (NeuN), lower astrogliosis, and reduced microglial response (GFAP and Iba1 fluorescence levels and Scholl morphometric analysis of individual astrocytes) after both peripheral and central administration of KA . Some of these effects are attributed to PRL, which is highly expressed during lactation and has been shown to have protective effects in both in vivo and in vitro experiments …”
Section: Discussionmentioning
confidence: 99%
“…Motherhood induces changes in the hippocampus that support the expression and maintenance of parental care behaviours . Regarding the neuroprotective effects of motherhood, we have previously reported that the hippocampus of the lactating dam is resistant to the damaging action of the excitotoxin kainic acid (KA), administered centrally or peripherally . The protective effect of the rat dam against excitotoxic lesions also has been documented by other groups .…”
Section: Introductionmentioning
confidence: 98%
“…Moreover, they increase neurogenesis within the subgranular zone of the dentate gyrus and subventricular zone (Pawluski et al, 2009), and induce regenerative responses in a mouse model of Alzheimer’s disease (Pike et al, 2009; Borowicz et al, 2011). During lactation, progesterone participates in glial changes in brain areas such as the cingulate cortex (Salmaso et al, 2009) and the dentate gyrus of the hippocampus (Cabrera et al, 2013), and this steroid is part of the hormonal cocktail responsible for diminished responses of astrocyte and microglial cells in the hippocampus of lactating rats to damage induced by excitotoxic insults (Cabrera et al, 2013). …”
Section: Hpa Axis Hormones Progesterone and Prolactin In The Regulamentioning
confidence: 99%